Definicje istnienia - Labenz, Piotr (Filozofia Nauki, 2001)
Since ontology is to be the science which studies that what exists, every ontological enterprise has to be preceded by an agreement as to what „existence” means. This is best done by giving a definition of existence. In the article the author examines definitions of existence that are used, or could be used, in various ontologies. To this aim he introduces a systematics of the possible definitions and with its help studies definitions of existence given by various authors. Definitions that he consid-ers have the form „<> <>”, where „p” is a sentence (it is also possible to treat existence as an undefined primary term, but such a treatment in the context of ontology in which it is used may be regarded as a contextual definition). Thus, in fact the subject of the analysis is what is understood by the expression of the form „x exists”.